Effect of occlusal contact of the loading rod tip on the fracture strength of ceramic crowns - Wilson B Mendes; Simonides Consani; Lourenço Correr-Sobrinho; Mario A C. Sinhoreti; Rafael L X. Consani (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study was to verify the effect of the occlusal contact of the rod tip on the fracture strength of crowns made with different ceramic systems. Materials and Methods: Conical preparation was performed on bovine teeth with diamond burs in mechanical lathe, and crowns were made for all-ceramic, metal-ceramic, In Ceram, and IPS Empress 2 ceramic systems according to manufacturers' instructions in prosthetic laboratory. The crowns were fixed with resin-modified glass ionomer cement or dual-curing composite resin under a static load of 4 kg for 1 min. To simulate the clinical contact between loading and ceramic crowns, the rod tip was made in accordance with the occlusal form of the ceramic crown. After storage in distilled water at 37°C for 24 h, the samples were submitted to 60,000 mechanical cycles at a load of 35 N/2 Hz immersed in distilled water. The fracture strength test was performed in an Instron with a cross-speed of 0.5 mm/min. Results: Data submitted to one-way ANOVA for randomized experiments followed by Tukey's test (α = 0.05) showed greater value for IPS Empress 2 (208.12 kgf) with significant difference in relation to all-ceramic (149.32 kgf) and In Ceram (142.25 kgf), whereas metal-ceramic showed intermediary value (182.83 kgf). Conclusion: The loading of the rod tip in occlusal contact with the crown did not promote premature failures during the mechanical fatigue test, and two-ceramic systems showed different values of fracture strength after mechanical fatigue test, with better performance for crowns manufactured with IPS Empress 2.